Defining Artificial Intelligence: A DeepSeek-Assisted Synthesis of Contemporary Definitions - Ananias C. Sabijon Jr.; Jonali E. Gonzales (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The rapid proliferation of Artificial Intelligence (AI) across virtually all educational, industrial and consumer domains is undeniable and well-documented. It has become a transformative force across all sectors of society, driving innovation in healthcare, finance, manufacturing, and communication. In education, AI increasingly influences teaching, learning, and educational leadership, reshaping pedagogy and knowledge access. Despite widespread adoption, the term remains variably defined across disciplines, creating conceptual ambiguities. This study aimed to develop a definition of AI, aided by the AI chatbot DeepSeek, by synthesizing definitions and descriptions from various authors from purposively selected peer-reviewed journals and to systematically describe the core conceptual parts that comprise the synthesized definition of AI, and to critically examine how the corresponding scholarly references theoretically corroborate each of the constituent elements. To achieve the objectives of the study, the researchers conducted a purposive literature search and analysis of the definitions and/or descriptions of Artificial Intelligence, then used the AI chatbot DeepSeek to develop the synthesized definition. Additionally, the researchers reviewed the parts of the synthesized definition alongside their corresponding published references to verify their alignment and validity. AI refers to a computational systems that perform cognitive tasks—including learning, reasoning, problem-solving, perception, and natural language understanding—typically associated with human intelligence. These systems operate through algorithmic processing of data and models, and with varying degrees of autonomy, adapt to environments, make predictions or decisions, and pursue goal-oriented behavior. Moreover, valid related references support each part of the synthesized definition.